FEMINISM SPIRIT’S REFLECTIONS ON ‘JORDAN O’NEIL’ IN G.I JANE MOVIE - Juli Yohana Zebua; Sri Minda Murni (State University of Medan, 2015)
This study deals with feminism Spirit’s reflections on ‘Jordan O’Neil’ in G.I Janemovie. The study is conducted by using descriptive qualitative approach. Theobjectives of the study are to find out kinds of oppression faced by O’Neil and herfeminism spirit’s reflections in term of oppression that she had faced. The data arecollected from dialogues and scenes in the movie. The object of the study isJordan O’Neil as the female main character. The study revealed that there arethree major oppressions faced by O’Neil according to Young’s theory: beingmarginalized,exploited and experiencing powerlessness. Feminism Spirit’sreflections on Jordan O’Neil in term of oppression that she had already faced arethree major parts: being persistent, independent, and courageous.